Penguatan Kompetensi SDM dan Motivasi Kerja pada UMKM Kopi di Labuan Bajo melalui Manajemen Sumber Daya Manusia Berbasis Komunitas - Filda Khoirun Nikmah; Bagas Gumintang (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
The rapid development of coffee MSMEs in Labuan Bajo, driven by its status as a Super Priority Tourism Destination, highlights the urgent need for better human resource management (HR) practices. Many of these MSMEs still operate HR structures informally, without clear job descriptions, performance evaluations, or motivation systems—which ultimately leads to unclear roles and low employee morale. This community service program aims to strengthen human resource competencies and employee work motivation through a Community-Based Human Resource Management (CBHRM) approach. Interventions were carried out through participatory training, co-designing HR tools (such as visual job descriptions and performance scorecards), as well as structured feedback mechanisms in several selected coffee MSMEs. The results show increased role clarity, stronger engagement, and more effective teamwork. In addition, employee involvement in HR planning helps drive innovation and strengthen organizational culture. The CBHRM model has proven to be effective in aligning local cultural values with practical HR solutions, as well as driving sustainable productivity and job satisfaction.